PORTRAIT OF COURT PROCEEDINGS IN THE WORK NIGHT AND DAY - Davlatova Shakhnoza Mukhammadievna (Western European Studies, 2025)
This article analyzes the literary depiction of court proceedings in Uzbek prose, its social and moral content. Court scenes are depicted in literature as complex processes related to the human psyche, justice, truth and conscience. In particular, in the work of Abdulla Qodiriy, social inequality, spiritual crisis and psychological pressures are depicted through the trial. The article extensively covers the literary style, artistic meaning and role of these scenes in society.
Keywords: Uzbek literature; court proceedings; justice